A composite measure of healthy lifestyle: A study from 38 countries and regions from Europe and North America, from the Health Behavior in School‐Aged Children survey. Issue 6 (11th April 2020) - Marques, Adilson; Bordado, Joana; Tesler, Riki; Demetriou, Yolanda; Sturm, David J.; de Matos, Margarida Gaspar
Abstract: Introduction: This study aimed to create a composite measure of a healthy lifestyle for adolescents, and analyze its relationship to sociodemographic factors. Methods: Data were from the Health Behavior in School‐Aged Children 2014 International survey. Participants were 167 021 adolescents (48.2% boys and 51.8 girls), aged 10‐16 years, from 38 countries. Results: Five healthy behaviors used in this study included engaging in ≥60 minutes of physical activity every day, daily consumption of fruit and vegetables, spending <2 hours daily immersed in screen‐based behaviors, and abstinence from alcohol as well as from tobacco products. Only 1.9% (95% CI: 1.4%, 2.3%) of adolescents had a healthy lifestyle, achieving all five healthy behaviors. In contrast, 4.2% (95% CI: 3.7%, 4.6%) reported none of the healthy behaviors. Conclusions: Despite the benefits of engaging in physical activity, engaging in low levels of screen‐based activity, regular consumption of fruits and vegetables, and abstaining from alcohol and cigarettes, only 2% of adolescents could be classified as having a healthy lifestyle.